ORGANIZATION OF MEDICAL AID DURING ANTHRAX OUTBREAK IN YAMALO-NENETS AUTONOMOUS DISTRICT IN 2016 - A. A. Ploskireva; L. G. Goryacheva; I. V. Lapenko; V. V. Maleev (Проблемы особо опасных инфекций, 2017)
The efficiency and timeliness of medical care of infectious patients are largely determined by the promptness of diagnosis and the rational organization of medical sorting of patients and contact persons. In 2016 there were 36 anthrax cases in the Yamal. In the immediate area of the epidemic were 327 people, including 135 children, in the endangered area – 539 people, including 217 children. Organization of medical care for patients and contact persons was accompanied by objective difficulties associated with the vastness of the territory under threat of infection spread, the presence of atypical and rare clinical forms of anthrax. Тhe article presents the analysis of actions for rendering of medical aid to patients with anthrax in the Yamal in 2016, and the proposed algorithms in medical triage and the organization of the emergency unit.